(untitled) (Research, Society and Development, 2020)
The STEM methodology has been used by several schools and universities around the world with the objective of getting students involved in solving real problems in a multidisciplinary way. An innovative methodology in which there is an idea of disruption with passive traditional teaching, in which the student has little interaction with the object of study and sees no connections with the world, with his daily lives. It was born in the United States of America from the need to train qualified professionals in the STEM areas: Science, Technology, Engineering and Mathematics. The proposal reaches other countries and as a result STEM Education becomes a topic of discussion in political, economic and educational circles around the world. In Brazil, the movement in favor of STEM Education is still timid when compared to the attention given in several countries. Thus, a question emerges: so far, what is there of scientific academic productions about STEM and Higher Education? Therefore, this article deals with a bibliographic review on STEM in Higher Education, as well as the analysis of this approach as an innovation in teaching. It was found that the amount of scientific productions related to STEM in Higher Education is still considered minimal due to the importance and applicability of the theme. No studies were found that discuss the application of STEM in Higher Education, however there are studies that focus on basic education, teacher training and interdisciplinarity, the latter being major challenges in the application of the methodology.